Case report: Short-long-short mechanism triggering sustained ventricular tachycardia in a patient with a single-chamber ICD but inhibiting antitachycardia therapy - Schernthaner, Christiana; Topf, Albert; Motloch, Lukas J.; Kraus, Johannes; Hauptmann, Laurenz; Hoppe, Uta C.; Strohmer, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
Introduction Short-long-short (SLS) sequences are an important cause of ICD pro-arrhythmia and can initiate both polymorphic and monomorphic ventricular tachycardias (VT). Depending on the programming of a single-chamber ICD, the interplay between SLS sequences and combined VT detection criteria can be responsible for withholding adequate anti-tachycardia pacing (ATP) or shock therapy. Methods A 78-year-old patient with ICD was admitted to our emergency department after external cardioversion of a long-lasting VT with hemodynamic compromise. The interrogation of the ICD revealed an SLS sequence initiating a monomorphic VT at a rate of 171 bpm (350 ms). The VT discrimination of the implanted single-chamber ICD was based on the onset and stability criteria as the patient had a history of paroxysmal atrial fibrillation. The ICD was programmed that both criteria had to be met for VT detection and initiation of anti-tachycardia therapy. Results Due to the SLS sequence in combination with the programmed VT detection interval, the onset threshold was not fulfilled and inhibited adequate therapy. Some relatively slow VT beats following the SLS sequence resulted finally in a considerable delay in the declaration of the episode onset. As a first step, the threshold for VT detection was programmed to 150 instead of 160 bpm. To avoid SLS sequences and pause-dependent ventricular tachyarrhythmias, VVI backup stimulation was increased from 35 to 55 ppm. Besides, a device-specific algorithm called rate smoothing was activated as a potential preventive feature. On the 3-month follow-up, all sustained VT episodes were detected adequately by the reprogrammed device, resulting in appropriate anti-tachycardia pacing. After further refinement and less aggressive programming of rate smoothing, the patient remained free of symptoms and arrhythmias over a follow-up of more than 2.5 years, particularly since progression to permanent atrial fibrillation and pacing at a lower rate of 60 ppm. Conclusions SLS sequences may initiate or trigger VT episodes. Misclassification of the true onset may occur in some ICD devices due to specific programming of VT detection criteria. If both criteria “Onset and Stability” have to be fulfilled, ICD therapy is not delivered despite ongoing VT. Anti-bradycardia backup pacing at a very low stimulation rate may facilitate SLS sequences in patients with ICD resembling a potential pro-arrhythmic mechanism. In case of gradual VT onset with some intervals slower than the programmed VT threshold, the detection rate has to be adjusted down to guarantee appropriate identification of the onset.